Monetizing French Distance Education: A Field Enquiry on Higher Education Value(s) - Marty, Olivier (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
A field enquiry in French distance education allows us to analyze the evolution of a specific institution towards new public management: Parallel to a trend of free courseware and open education, there is a paradoxical reality of distance education monetization. Whereas history shows how traditional French education is a state controlled public good, a new policy is changing the organization’s culture towards a commercial and industrial activity. From inside the institution, we describe the cultural changes, with its human resources, accounting, and marketing dimensions. We relate debates about the institution’s business model within the economy of knowledge – selling either services or contents, focusing on the learner’s experience. Lastly, we analyze the notion of value underlying this monetization of a distance education institution: both the computing of a specific training’s value and the shared values of the workers binding up their collective identity.